CHARACTERISTICS OF PROTEOLYTIC VASOACTIVE SYSTEMS IN CHILDREN OF EARLY AGE WITH INFECTIOUS DISEASES OF URINARY TRACT - I.R. Egorova; E.I. Kondrat'eva; A.A. Terent'eva; G.A. Sukhanova ("Paediatrician" Publishers LLC, 2008)
He structure of microbial inflammatory diseases of urinary tract in children of early age is described in this article. Clinical course of infectious diseases of urinary tract in first 3 years of life is characterized by absence of specific clinical features. Increase of activity of kallikrein and angiotensin converting ferment, and decrease of callikreinogen and α-2-macroglobulin testify to infectious process in kidney in children of early age. Increase of excretion of albumin with urine in patients with nephropathy is an evidence of glandular lesion at microbial inflammatory process in renal tissue.Key words: children, infection of urinary tract, microalbuminuria, kallikrein, kallikreinogen, angiotensin_converting enzyme, α-2-macroglobulin.